The Relationship Between Procedures of Management Accounting and Internal Control - M. A. Vakhrushina; M. A. Prunenko (Учёт. Анализ. Аудит, 2020)
The article substantiates the objectively growing importance of internal control and management accounting systems in the context of an impending global financial and economic crisis. The research methodology is based on the application of historical analysis and synthesis methods, systemic and logical approaches, the method of analogies and groupings. The research defines the place of managerial accounting in the organization’s internal control system, identifies the procedures for these systems and the sequence of their practical implementation. The authors determine the possibilities and ways of incorporating management accounting procedures into internal control procedures and draw a conclusion about the existing duplication of some of them. The article substantiates the principles compliance with which will ensure the success of the implementation under discussion. The results of the study can be useful in the process of setting up and developing systems of internal control and management accounting in Russian business structures, primarily representing small and medium businesses.